2001
DOI: 10.1117/12.435826
|View full text |Cite
|
Sign up to set email alerts
|

<title>Investigation of thermal annealing by gamma irradiation at room temperature in LiNbO<formula><inf><roman>3 </roman></inf></formula>crystals</title>

Abstract: An interesting phenomenon of thermal annealing in gamma irradiated undoped, and photorefractive Cu-and Fe-doped, Zoriented LiNbO 3 crystals has been observed. Prior and after each gamma irradiation the crystals were thermally annealed in the air at 800'C for a couple of hours. Optical homogeneity was investigated on the entire areas of LiNbO 3 wafers by measuring distributions of birefringence, the principal azimuth, transmission, and parameters associated with birefringence dispersion, and also by measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…that thermal annealing in air in a resistant-heated chamber led to a noticeable decrease in the optical homogeneity, while this effect has later been cured by gamma irradiation. In [15], it has been suggested that a certain optical inhomogeneity involved in these heat treatments could be associated with temperature gradients in LiNbO 3 wafers, and was always present especially when the samples after the thermal annealing had been cooled down to room temperature. These gradients through the pyroelectric and electrooptic (also secondary electrooptic or piezo-electrooptic) effects could just be the primary source for the induced birefringence.…”
Section: Methodsmentioning
confidence: 99%
“…that thermal annealing in air in a resistant-heated chamber led to a noticeable decrease in the optical homogeneity, while this effect has later been cured by gamma irradiation. In [15], it has been suggested that a certain optical inhomogeneity involved in these heat treatments could be associated with temperature gradients in LiNbO 3 wafers, and was always present especially when the samples after the thermal annealing had been cooled down to room temperature. These gradients through the pyroelectric and electrooptic (also secondary electrooptic or piezo-electrooptic) effects could just be the primary source for the induced birefringence.…”
Section: Methodsmentioning
confidence: 99%